Molecular Correlates of Long Survival in IDH-Wildtype Glioblastoma Cohorts. Issue 8 (10th July 2020) - Galbraith, Kristyn; Kumar, Ashwani; Abdullah, Kalil G; Walker, Jamie M; Adams, Steven H; Prior, Timothy; Dimentberg, Ryan; Henderson, Fraser C; Mirchia, Kanish; Sathe, Adwait Amod; Viapiano, Mariano S; Chin, Lawrence S; et al.
Abstract: IDH-wildtype glioblastoma is a relatively common malignant brain tumor in adults. These patients generally have dismal prognoses, although outliers with long survival have been noted in the literature. Recently, it has been reported that many histologically lower-grade IDH-wildtype astrocytomas have a similar clinical outcome to grade IV tumors, suggesting they may represent early or undersampled glioblastomas. cIMPACT-NOW 3 guidelines now recommend upgrading IDH-wildtype astrocytomas with certain molecular criteria ( EGFR amplifications, chromosome 7 gain/10 loss, and/or TERT promoter mutations), establishing the concept of a "molecular grade IV" astrocytoma. In this report, we apply these cIMPACT-NOW 3 criteria to 2 independent glioblastoma cohorts, totaling 393 public database and institutional glioblastoma cases: 89 cases without any of the cIMPACT-NOW 3 criteria (GBM-C0) and 304 cases with one or more criteria (GBM-C1-3). In the GBM-C0 groups, there was a trend toward longer recurrence-free survival (median 12–17 vs 6–10 months), significantly longer overall survival (median 32–41 vs 15–18 months), younger age at initial diagnosis, and lower overall mutation burden compared to the GBM-C1-3 cohorts. These data suggest that while histologic features may not be ideal indicators of patient survival in IDH-wildtype astrocytomas, these 3 molecular features may also be important prognostic factors in IDH-wildtype glioblastoma.